THE BEHAVIOURS AND JOB POSITIONS OF CITIZENS IN SMART CITIES’ DEVELOPMENT - Lim, Sengboon; Abdul Malek, Jalaluddin; Hussain, Mohd Yusof; Tahir, Zurinah (PLANNING MALAYSIA, 2019)
Of the three major actors in smart cities, citizens have the most ambiguous roles, unlike the government which is the clear decision-maker, and the private technological players which are obviously supposed to provide state-of-the-art technologies to smart cities. Evidently, the possession of ambiguous characteristics or vague roles can result in the manipulation and subjugation of the general public by the power-holders. Thus, the objective of this paper is to identify the desirable characteristics – including the behaviours and job positions – of the citizens who participate in the development of smart cities. Following the conduction of semi-structured interviews on the stakeholders of smart cities, it was found that citizens can actually be (1) active and independent volunteers in public life, (2) local champions or co-producers of public values, as well as (3) aware and educated-intention human sensors who drive changes, instead of being passive users of data or beneficiaries of services. It has been argued that the creation of smart cities is reliant on a deeper understanding of the citizens’ characteristics, apart from the implementation of policies which generate aware and civic-minded citizens.